Identification and Expression of Frizzled-3 Protein in Rat Frontal Cortex After Antidepressant and Electroconvulsive Treatment - Misa Yamada; Tomoko Iwabuchi; Kou Takahashi; Chika Kurahashi; Hisayuki Ohata; Kazuo Honda; Teruhiko Higuchi; Mitsuhiko Yamada (Elsevier, 2005)
The biological basis for the therapeutic mechanisms of depression are still unknown. While performing EST (expressed sequence tag) analysis to identify some molecular machinery responsible for the antidepressant effect, we determined the full-length nucleotide sequence of rat frizzled-3 protein (Frz3) cDNA. Interestingly, Northern blot analysis demonstrated that elevated levels of Frz3 were expressed continually from embryonic day 20.5 to postnatal 4 weeks in developing rat brain. In adult rat brain, Frz3 mRNA was expressed predominantly in the cerebral cortex and hypothalamus and moderately in the hippocampus. Using real-time quantitative PCR, we demonstrated that chronic treatment with two different classes of antidepressants, imipramine and sertraline, reduced Frz3 mRNA expression significantly in rat frontal cortex. Electroconvulsive treatment (ECT) also reduced Frz3 expression. In contrast, antidepressants and ECT failed to reduce Frz2 expression. Additionally, chronic treatment with the antipsychotic drug haloperidol did not affect Frz3 expression. Recently, the Frz/Wingless protein pathway has been proposed to direct a complex behavioral phenomenon. In conclusion, the Frz3-mediated signaling cascade may be a component of the molecular machinery targeted by therapeutics commonly used to treat depression. Keywords:: gene expression, mRNA fingerprinting, imipramine, sertraline